Cannabis and Suicidal Behaviour Among Adolescents: A Pilot Study from Trinidad - Hari D. Maharajh; Monique Konings (The Scientific World Journal)
Cannabis use and suicidal behaviour are causes of adolescent morbidity and mortality worldwide. Changing trends in these behaviours in younger age groups, higher incidence, gender differences and sociocultural variations present an enormous challenge. There is no consensus whether these complex relationships are either a direct or an indirect effect due to other mental disorders, or a social response of disclosure of drug taking habits to family members and school authorities. This paper reviews the epidemiology of suicidal behaviour and cannabis use among adolescents and looks at the relationship of these behaviours regionally and internationally. The Caribbean islands have an established use of cannabis with higher suicidal rates, which provides an ideal setting to investigate the interrelationship of these disorders. Preliminary research findings in Trinidad indicate high rates of cannabis use among school students with higher rates in vocational schools compared to grammar schools. Utilising the CAPE questionnaire, depressive and psychotic experiences were common findings in adolescent cannabis users with a significant preponderance of depressive experiences (p<0.01). Our findings suggest that there is a convincing relationship between suicidal behaviour and cannabis use, the latter awakening depressive experiences. Suicidal behaviour and cannabis use are major public health problems and require a multidimensional approach with culturally competent preventive interactions. School based prevention programmes are necessary at the levels of parent-teacher partnership and classroom intervention. The treatment of adolescent disorders remains a major challenge of the future. Double disorders such as cannabis use and suicidal behaviour are uncharted areas and need novel approaches.